Ultrasonic testing of selectively laser melted parts - Teo, Zhi Jie (2017)
Additive manufacturing (AM) has revolutionise the manufacturing industry in recent years. It minimises the time and cost as compared to conventional manufacturing procedures. AM also accommodates to consumer’s rapid changing of choices in products. The key concept of AM is the layer-by-layer of material addition process which differs from conventional methods of subtracting material. As AM emerges as an upcoming trend in current world technology, several procedures and process parameters are still lack in the area of standardisation. These limitations remained as a challenge for industries to overcome and produce parts that are free from defects. Porosity level of the end product is of the greatest importance to the manufacturers. It discloses the material properties and microstructure of the end product. Thus, all the industries have to make sure that the parts fabricated with AM are structurally safe for use in different types of operation.